Prevalence of Vibrio alginolyticus in Sediment Samples of River and Coastal Areas of Bangladesh (Bangladesh Journal of Microbiology, 2016)
Vibrio alginolyticus has been thought to be a halophilic marine bacterium that causes diarrhea, otitis media and wound infection through the consumption of raw or inappropriately cooked sea food. It is one of the main Vibrio pathogens affecting marine animals, such as marine fish, shrimp and shellfish which lead to large economic damage. Although there are reports on the presence of this organism in the coastal area of other countries, not so much work has been done on the isolation and characterization of this species in Bangladesh. The present study was, therefore, undertaken to isolate and characterize V. alginolyticus organisms isolated from the rivers (fresh water) and estuaries (brackish water) of Bangladesh. A total of 9 isolates of Vibrio species were obtained from different water bodies (three from Meghna river, two from Shangu river and four from estuary) and provisionally identified as Vibrio alginolyticus following standard biochemical tests. All these 9 strains showed same pattern of antibiotic resistance to ampicillin, streotomycin, penicillin, but sensitive to nalidixic acid. In the virulence properties test, two isolates showed positive results for toxR gene and none of the isolates showed positive results for tdh gene. Challenge experiments in Singhi fish (Heteropneustes fossi) with the live cells and the culture filtrate prepared from the V. alginolyticus showed high mortality of the fish population. All these studies suggest the presence of pathogenic V. alginolyticus strains in the river water and estuarine bodies of Bangladesh and the extracellular toxin(s) of the V. alginolyticus might be one of the causes for fish mortality.Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 1-6